2011
DOI: 10.1063/1.3585831
|View full text |Cite
|
Sign up to set email alerts
|

Pb loss in Pb(Zr,Ti)O3 ceramics observed by in situ ionic conductivity measurements

Abstract: Analysis of the impedance spectra of Nb-doped Pb(Zr,Ti)O3 (PZT) embedded capacitors revealed that the ionic conductivity increased monotonically during annealing at 700 °C. Furthermore, the rate of increase was lowered by a reduction in the ambient pO2. The results could be explained by a model in which oxygen vacancies are generated as a consequence of Pb evaporation from the PZT. At 700 °C, this process is most likely limited by surface kinetics rather than Pb bulk diffusion. It was shown that the Pb loss co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…5 Volatilization of PbO is problematic during annealing (600-800 C), and is only partially controlled for thin films through the use of rapid thermal annealing processes. [6][7][8][9] In thin films, PbO control has been achieved either by increasing the PbO content in the deposited film 6 (typically by 5%-20% excess PbO in solutions for solution processing and in targets for physical vapor deposition) or by adding a PbO overcoat after the film has been prepared and heating to diffuse the PbO into the PZT film. 5,10 Excess surface PbO can be removed using an acetic acid wash. 10 In both cases, the PbO content is essentially controlled by kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…5 Volatilization of PbO is problematic during annealing (600-800 C), and is only partially controlled for thin films through the use of rapid thermal annealing processes. [6][7][8][9] In thin films, PbO control has been achieved either by increasing the PbO content in the deposited film 6 (typically by 5%-20% excess PbO in solutions for solution processing and in targets for physical vapor deposition) or by adding a PbO overcoat after the film has been prepared and heating to diffuse the PbO into the PZT film. 5,10 Excess surface PbO can be removed using an acetic acid wash. 10 In both cases, the PbO content is essentially controlled by kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…A more comprehensive study on rare earth doping can be found in [25]. It was also shown that donor doping does not lead to complete annihilation of the p-type conduction behaviour in PZT and furthermore does not entirely suppress the formation of oxygen vacancies [26,27,28,29,30,31]. Oxide ion motion was analysed for undoped and donor doped PZT as well as co-doped PZT with donor excess [32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that care must be taken to ensure PbO is not driven out of the PZT itself. Measurements of conductivity in PZT ceramics at 700°C have shown an increase in ionic conductivity as a result of the [38]. The presence of oxygen vacancies within the films may ultimately limit the lifetime of the actuators.…”
Section: Resultsmentioning
confidence: 99%